Assessing the Quality Life of Elderly Individuals - Oconer, Sheila Marie; Quimen, Victor Jr. (MALATA SAINS INDONESIA, 2024)
Introduction: Quality of life is very important in people over the age of 60 due to its close relationship with satisfaction and achievement of personal goals.Objectives: The study aims to describe the quality of life among elderlies and to determine the factors that may influence it. Methods: The respondents are the 158 elderly (60 to 75 years old) residing in barangay West Bajac-Bajac, Olongapo City. The instruments used for this study are an adaptation of WHOQOL-BREF. The researchers applied a convenience sampling method when distributing a paper survey to the respondents in the community. Result: The results indicated that the majority of respondents were female, aged 61 to 70 years old, married, and high school graduates, with pensions as their primary source of income. The prevalence of hypertension was high among the respondents, whereas participation in programs by the Office of Senior Citizens Affairs (OSCA) was low. Among the four QoL domains, the physical health domain had the highest mean score, reflecting satisfactory mobility and ability to perform daily activities. In contrast, the social relationships domain had the lowest score, particularly in sexual satisfaction. Psychological health showed positive self-acceptance but occasional negative feelings, while environmental health was significantly associated with sex differences. The findings emphasize the importance of a holistic approach to improving the QoL of the elderly, focusing on physical health, psychological well-being, and strengthening social connections. Conclusion: The study recommends implementing integrated community-based health programs tailored to the elderly's needs, enhancing social participation, and addressing gaps in healthcare access. Future research should expand the study scope to other regions and include broader demographic representations.